Family and Government Support for Health Community in To Balo and To Kribo - Muhtar Lutfi; Nur Hidayah; Ummu Alfatimah; A Adriana Amal; Syamsiah Rauf (Journal of Health Science and Prevention, 2019)
The purpose of this study was to find out family and government support to the community to Balo and to Kribo on health based on social factors and family attachments (kindship and social factors) in the Leininger sunrise enabler. This study uses a qualitative method with an ethnographic approach and representative based sampling as a sampling technique. The subject of this research was the community of To Balo and To Kribo. How to collect data by observation, in-depth interviews, and documentation. The techniques of data analysis and processing employedontent analysis with stages: making data transcripts, determining meaning units, summarizing and organizing data, doing data abstractions, identifying variables and relationships between variables qualitatively, and drawing conclusions. Validating data used source triangulation. The results show that obtained after conducting research on the community of to Balo and to Kribo stated that sickness and health were influenced by family and community support (local government). Both provide a large role in accessing health services.